2016
DOI: 10.25215/0304.166
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being among University Students: A Comparative Study

Abstract: Discovering new constructs in the field of psychological health, positive psychology has been successful to introduce new resistance resources for coping with the stressful events, especially at universities students. Positive psychology, as a modern approach, emphasizes on perception and interpretation of happiness and well-being and prediction of the factors related to them as well. Psychological well-being is a multi-dimensional concept; optimism, self-control, happiness, sense of interests, free of failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…If not handled properly, this can have negative effects on an individual's mental health. Positive emotional and social support, on the other hand, is critical in developing psychological well-being (Siddiqui et. al., 2016).…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…If not handled properly, this can have negative effects on an individual's mental health. Positive emotional and social support, on the other hand, is critical in developing psychological well-being (Siddiqui et. al., 2016).…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…Research has shown that positive emotional and social support plays a fundamental role in building the psychological well-being (Siddiqui & Khan, 2016). Individuals who have high psychological well-being will lead a happy life and will be satisfied with their professional and personal life, capable and well-supported (Panahi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the lives of postgraduate students, their academic life cannot be overlooked. Siddiqui and Khan (2016) stated that for people to achieve psychological well-being, there is the need to have a good relationship with others, appreciate the environment, accepting themselves and the past, have a goal in life, strive to develop and make their own decisions. Postgraduate students in their quest for educational attainment is predicated on their academic achievements and academic success which is regarded as one of the major life accomplishment and key determinants of life.…”
Section: Introductionmentioning
confidence: 99%